Proyecto de factibilidad para la producción y comercialización de Snacks de garbanzo en la ciudad de Loja - Jimbo Ordoñez, Gissela Raquel (2023)
The development of the present research work has aims to create a company producing chickpea snacks in Loja city, it was done based on the following objectives: to conduct a market study to determine supply, demand and unsatisfied demand, as well as to propose marketing strategies. A technical study, to determine the size and location, and engineering of the project and propose the organic-functional structure of the company. An economic-financial study was carried out to prepare cost and revenue budgets, break-even point and financial statements. Finally, a financial evaluation was carried out to determine the feasibility of the project through financial indicators, net present value, internal rate of return, capital recovery period, benefit-cost ratio and sensitivity analysis. The research approach is quantitative, exploratory and descriptive, for which methods such as deductive and descriptive were used, as well as techniques that allowed the collection of information. Subsequently, the analysis of the different studies was carried out. In the market study, an unsatisfied demand of 29,744,424 grams of snack for year 1 was obtained; in the technical study, the capacity used is 235,733 units per year; the investment required to carry out the project is US$32,703.80. The retail cost for the first year is 0.70 ctvs, with respect to the financial evaluation the following was obtained; Net Present Value of 42,907.6; Internal Rate of Return of 54.19%; Capital Recovery Period of 1 year 11 months 19 days; Benefit-Cost Ratio of 1.15 and finally the Sensitivity Analysis with an increase in costs of 5.11% and a decrease in income of 4.44%. Therefore, based on the pertinent economic analysis, it is concluded that the project is viable and feasible.